2021
DOI: 10.1093/pubmed/fdab344
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-adoption of healthy behavior among individuals with diabetes: a population-based study in Brazil

Abstract: Background The non-adoption of behavioral changes to control diabetes mellitus contributes to a low adherence to self-care. This study aimed to investigate the factors associated with non-adoption of healthy behaviors among diabetic individuals. Methods Cross-sectional study using data from the National Health Survey (Pesquisa Nacional de Saúde) carried out in 2013 in Brazil, with adults (≥18 years) (n = 3098). The outcome va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A recent study has shown that not making regular doctor visits increases the chance of Brazilians with diabetes not engaging in healthy behaviors independently of sex, age, schooling, and economic status 48 . Similar results were also observed among hypertensive individuals 49 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that not making regular doctor visits increases the chance of Brazilians with diabetes not engaging in healthy behaviors independently of sex, age, schooling, and economic status 48 . Similar results were also observed among hypertensive individuals 49 .…”
Section: Discussionmentioning
confidence: 99%